PERAN LAYANAN BK DALAM PEMILIHAN JURUSAN KULIAH PADA SISWA KELAS XII MA NURUL HUDA CIREBON - Zahwa Ardhinia Naisa; Anggun Setiani; Rahmi Anekasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Choosing a college major is a crucial decision that will impact a student's future. However, many students remain confused about choosing a college major that aligns with their interests, talents, and abilities. This study aims to analyze the perspectives of 12th-grade students at MA Nurul Huda Cirebon on the role of Guidance and Counseling services in choosing a college major. The study used a qualitative method with a descriptive approach. The subjects were 12th-grade students at MA Nurul Huda Cirebon, selected using a purposive sampling technique. Data collection was conducted through an open-ended questionnaire distributed using Google Forms. The results showed that students experienced confusion in choosing a college major due to a lack of information regarding study programs, career prospects, understanding of their potential, and the discrepancy between students' interests and parents’ expectations. Guidance and Counseling services are considered to play a crucial role in assisting students by providing information on further study, individual consultations, and career guidance. Furthermore, guidance and counseling services also help increase students' confidence in making decisions regarding their college major choices. Thus, guidance and counseling services play a crucial role in helping students understand their potential, reduce confusion, and determine a college major that aligns with their interests, talents, and career goals.